Disparities of healthcare utilization in sexually transmitted diseases management: focusing on racial/regional variances with U.S. national inpatient sample in 2016–2019 - Jeong-Hui Park; Ji Eun Kim; Seohyun Woo; Sun Jung Kim; Sun Jung Kim (Frontiers in Public Health)
ObjectiveTo identify patient and hospital factors, such as race and region, associated with increased sexually transmitted diseases (STDs) hospital charges, and emergency room (ER) usage for significant federal funding and research allocation.MethodsThe National Inpatient Sample (NIS) of the United States was used to identify patients with STDs (weighted n = 22,275) from 2016 to 2019. The sample's characteristics, the odds of an ER visit, and the association between an ER visit and healthcare utilization measured by hospital charges were examined by multivariate logistic regression and linear regression.ResultsAmong 22,275 national inpatients, 74% had ER visits. The number of inpatients with STDs, ER visits, and average hospital charges continuously increased during the study period. Survey logistic results showed that sex, insurance type, and geographic region were associated with higher odds of ER visits among patients. The survey's linear results demonstrated that ER visits, Hispanic ethnicity, insurance type, and specific geographic regions were associated with higher hospital charges.ConclusionsMultiple factors are related to increased healthcare costs among patients with STDs, such as ER usage, Hispanic ethnicity, and insurance type. Policy efforts should focus on reducing ER dependency through targeted outreach, improving access to preventive care, and addressing disparities based on ethnicity and insurance status to reduce healthcare costs for vulnerable populations.